Interactions between policy effects, population characteristics and the tax-benefit system: An illustration using child poverty and child related policies in Romania and the Czech Republic - Silvia Avram; Eva Militaru (University of Essex, Institute for Social and Economic Research (ISER), 2015)
We investigate the impact of the Romanian and Czech family policy systems on the income distribution and poverty risk of families with children. We focus on separating out the effects of the policy design itself, size of the benefits and the interaction between policies and population characteristics. We find that interactions between population characteristics, the wider tax benefit system and child related policies are pervasive and large. Both population characteristics and the wider tax-benefit environment can dramatically alter the antipoverty effect of a given set of policies.
Keywords: D31; H53; I38; 330; child poverty; child benefits; microsimulation; policy interactions; population interactions